Islamic Law In Morocco: Study on The Government System and The Development of Islamic Law - Muannif Ridwan; Ahmad Syukri Saleh; Abdul Ghaffar (ARRUS Journal of Social Sciences and Humanities, 2021)
This study discusses Islamic law in Morocco. The author focuses on the study of the government system and the development of Islamic law there. This study used descriptive qualitative method or so-called literature study /library research. Literature study examines data by exploring, observing, examining, and identifying existing knowledge in the literature to get a conclusion of truth, both philosophical and empirical. This study concludes that Morocco is a Muslim country, the population is more than 98% embraced Islam, the system of government is a democratic, social and constitutional monarchy that is based ongoverned by the 1972 constitution which was amended in 1980, 1992, and in September 1996. It has Mudawwana al-Usrah (2004) which is a contemporary family law in Morocco, family law which was originally still contained in fiqh books has become an implementing law. The legal system in Morocco is divided into two types of judiciary; Shari'a Court and Madaniyah Court (General Court). The existence of the renewal of private law (akhwal syakhsiyah) is guided by three principles, first, the principles and foundations of family law that are applied are the Maliki Mazhhab, second, paying attention to aspects of maslahah mursalah, third, the laws imposed in other Muslim countries The Moroccan government allows abortion for cases of rape and incest or incest or serious defects and incurable diseases of the fetus. last, Morocco is a country that allows polygamy. The issue of polygamy is regulated in the 1958 family law law Article 30 paragraph (1).